Asteroseismology of Solar-Type Stars with K2: Detection of Oscillations in C1 Data. (4th January 2016) - Chaplin, W. J.; Lund, M. N.; Handberg, R.; Basu, S.; Buchhave, L. A.; Campante, T. L.; Davies, G. R.; Huber, D.; Latham, D. W.; Latham, C. A.; Serenelli, A.; Antia, H. M.; et al.
Abstract: We present the first detections by the NASA K2 mission of oscillations in solar-type stars, using short-cadence data collected during K2 Campaign 1 (C1). We understand the asteroseismic detection thresholds for C1-like levels of photometric performance, and we can detect oscillations in subgiants having dominant oscillation frequencies around 1000 μHz. Changes to the operation of the fine-guidance sensors are expected to give significant improvements in the high-frequency performance from C3 onwards. A reduction in the excess high-frequency noise by a factor of 2.5 in amplitude would bring main-sequence stars with dominant oscillation frequencies as high as ≃2500 μHz into play as potential asteroseismic targets for K2 .